2019
DOI: 10.1186/s40538-019-0170-3
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth stage influences heavy metal accumulation in leafy vegetables of garden cress and sweet basil

Abstract: Background: Contamination of vegetable crops with heavy metals is a great threat to human health. On the other hand, monitoring plant tissue content of heavy metals at different growth stages could have important implications. In this study, shoot and root samples of garden cress and sweet basil were collected from five farms, from heavy metal polluted fields located in Shahre Rey, south of Tehran, Iran, in either young (3 weeks old) or mature (7 weeks old) plants. The concentrations of cadmium (Cd), lead (Pb)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…Vegetables are considered essential diet components ( Wang et al., 2019 ), and can accumulate metals in concentrations higher than the maximum allowed levels, and due to fresh consumption, their contamination with heavy metals is very important in human health ( Souri et al., 2018 , 2019 ). In particular, the accumulation of Cr in edible parts of plants can cause numerous health risks for consumers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetables are considered essential diet components ( Wang et al., 2019 ), and can accumulate metals in concentrations higher than the maximum allowed levels, and due to fresh consumption, their contamination with heavy metals is very important in human health ( Souri et al., 2018 , 2019 ). In particular, the accumulation of Cr in edible parts of plants can cause numerous health risks for consumers.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the toxicity of Cr, this element can promote molecular, biochemical and ultrastructural changes in plant tissues ( do Nascimento et al., 2018 ). Plants can undergo chloroplast pigment degradation, reductions in photosynthetic activity, cell membrane damage and production of reactive oxygen species (ROS) under heavy metal contamination ( Hatamian et al., 2020 ; Souri et al., 2019 ; Tang et al., 2020 ). To protect against oxidative stress, plants affected by heavy metal induces enzymatic and non-enzymatic ROS scavenging systems, having the latter a crucial role in the cell defense, since they act as cofactors of antioxidant enzymes ( Gupta et al., 2019 ; Hu et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the reduction of K content in the shoot with increased aluminum levels occurs due to the competition of cations (Al and K + ) for absorption sites in the transporters or influx channels of monovalent and divalent cations, reducing both its translocation to the shoot or its energy supply for energy-dependent transportation systems (Kochian, 1995). It has been shown that heavy metals can significantly damage conducting vessels of plants including the transportation pathways from the roots to the stems and shoots (Hatamian, et al, 2020b;Souri;Tesfamariam, 2019), that probably Al with a similar effect can damper transportation vessels of plants.…”
Section: Resultsmentioning
confidence: 99%
“…The tolerance towards heavy metal stresses varies from specie to specie, stages of growth, and plant parts (Souri et al 2019). The performance of cultivars may vary because of different genetic makeups.…”
Section: Discussionmentioning
confidence: 99%